2021
DOI: 10.1186/s13287-021-02404-8
|View full text |Cite
|
Sign up to set email alerts
|

A novel therapeutic approach for inflammatory bowel disease by exosomes derived from human umbilical cord mesenchymal stem cells to repair intestinal barrier via TSG-6

Abstract: Background Exosomes as the main therapeutic vectors of mesenchymal stem cells (MSC) for inflammatory bowel disease (IBD) treatment and its mechanism remain unexplored. Tumor necrosis factor-α stimulated gene 6 (TSG-6) is a glycoprotein secreted by MSC with the capacities of tissue repair and immune regulation. This study aimed to explore whether TSG-6 is a potential molecular target of exosomes derived from MSCs (MSCs-Exo) exerting its therapeutic effect against colon inflammation and repairing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
102
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(103 citation statements)
references
References 50 publications
1
102
0
Order By: Relevance
“…We were able to successfully isolate and culture UC-MSCs from the fresh umbilical cord ( Zheng et al, 2020 ; Yang et al, 2021 ). The UC-MSCs displayed as spindle-shaped cells crawled out of the tissue pieces when the tissue blocks adhered to the bottom of the culture flask within the medium for 7–10 days ( Figure 2A ).…”
Section: Resultsmentioning
confidence: 99%
“…We were able to successfully isolate and culture UC-MSCs from the fresh umbilical cord ( Zheng et al, 2020 ; Yang et al, 2021 ). The UC-MSCs displayed as spindle-shaped cells crawled out of the tissue pieces when the tissue blocks adhered to the bottom of the culture flask within the medium for 7–10 days ( Figure 2A ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, intraperitoneal injection of MSC-Exo in a mouse model of inflammatory bowel disease indicated a protective role in the intestinal barrier not only by preventing the destruction of tight junctions, therefore decreasing permeability, but also by modulating the responses of Th2 and Th17 cells in the mesenteric lymph nodes. Again, the knockdown of TSG-6 abrogated the therapeutic effects of MSC-Exo; conversely, administration of a recombinant of TSG-6 showed beneficial effects similar to those of MSC-Exo ( 286 ). Therefore, TSG-6 appears to play a major role in the anti-inflammatory effects of MSC-EVs in inflammatory bowel pathologies.…”
Section: Immuno-properties Of Msc-evs and Mofmentioning
confidence: 94%
“…IBD, which primarily includes ulcerative colitis (UC) and Crohn’s disease (CD), has become a global disease with an increasing incidence ( 118 ). Studies of this disease have mainly used DSS and 2,4,6-trinitrobenzenesulfonic acid (TNBS) to induce IBD in mouse models ( 119 ). Existing drugs to treat IBD are still very limited, Therefore, there is an urgent need to develop safe and effective treatments for IBD ( 120 ).…”
Section: Applications Of Mesenchymal Stem Cell-derived Exosomes In Autoimmune Diseasesmentioning
confidence: 99%
“…hUC-MSC-EXOs also inhibited neddylation and alleviated IBD by miR-326 ( 122 ). Another study also showed that exosomal miRNA of MSCs, such us miR-146a, downregulated TNF receptor-associated factor 6 (TRAF6) and IL-1 receptor-associated kinase 1 (IRAK1) expression, inhibited pro-inflammatory cytokine and enhanced the expression of IL-10 ( 123 ).Moreover, tumor necrosis factor-α stimulated gene 6 (TSG-6), as detected by hUC-MSC-EXOs, regulated the immune response of Th2 and Th17 cells in mesenteric lymph nodes (MLN), down-regulated the levels of pro-inflammatory cytokines in colon tissue, and up-regulated the levels of anti-inflammatory cytokines to protect the intestinal barrier ( 119 ). Other tissue-derived MSC-EXOs showed similar efficacy to that of hUC-MSC-EXOs in the treatment of DSS induced IBD.…”
Section: Applications Of Mesenchymal Stem Cell-derived Exosomes In Autoimmune Diseasesmentioning
confidence: 99%